Collaborative Governance: Countering Narcotics Abuse in Indonesia - Syahrul Akmal Latif; Ranggi Febrian (Journal of Governance, 2022)
The collaboration of Government Institutions driven by BNN in narcotics countermeasures in Indonesia is quite successful in reducing the number of narcotics abuse. The problem is that in 2019 there was an increase in prevalence by 0.03%. Collaborative Governance is a strategy in overcoming narcotics in Indonesia, seen from 4 dimensions, namely the context of the collaboration process influenced by starting conditions, facilitative leadership, and institutional design. The quality method with a regular study approach from government reports and research results. In the context of the research conducted, the phenomenon of narcotics problems in Indonesia has long been the subject of the author's observations so things are found that are noted in the findings of the problem of narcotics abuse. The results of this study are three dimensions, namely starting conditions, facilitative leadership, and institutional design influencing the collaboration process with a positive output. As a result, there was a significant decrease in the prevalence of narcotics from 2011 to 2019.  In 2011 the prevalence was 2.23%, in 2014 the prevalence was 2.18%, in 2017 at 1.77%, and in 2019 at 1.80%.